Trends of mitochondrial changes in AD: a bibliometric study - Song, Ruiyao; Guo, Yunchu; Fu, Yu; Ren, Hongling; Wang, Hairong; Yan, Hongting; Ge, Yusong (Frontiers in Aging Neuroscience, 2023)
Background Alzheimer’s disease (AD) is a neurodegenerative disease characterized by progressive progress and memory loss, which eventually develops into dementia. It can cause personality disorders and decreased quality of life of patients. Currently, AD patients account for 60–70% of global dementia patients and the incidence rate of AD is increasing annually. AD not only causes pain to patients but also brings a heavy burden to the entire family. Studies have found that there is a connection between mitochondrial dysfunction and other biochemical changes in AD like classical neuropathological hallmarks (β-amyloid and tau protein), inflammation pathways, oxidative stress, and so on. Evidence shows that early treatment targeted directly to mitochondria could extend the lifespan of model mice and decrease the relevant neuropathological markers. Therefore, research on the mitochondrial dysfunction of AD can be of potential significance for clinical treatment. To date, few bibliometric analysis articles related to mitochondrial dysfunction of AD have been published. Bibliometric analysis refers to quantitatively analyzing certain aspects of articles like publishers, authors, and countries by using statistical and mathematical methods. Combined with statistical software, a large number of papers can be converted to visualization figures and tables, which provide vital information such as keyword hotspots and the names of contributing authors. Through the bibliometric analysis method, our study aimed to provide study trends and keyword hotpots for researchers to conduct further relevant research in this field. Methods We used the Web of Science core collection database as a literature retrieval tool to obtain data related to mitochondrial changes in Alzheimer’s disease during the last 20 years. The retrieval type was [TS = (Alzheimer’s disease)] ND [TS = (mitochondrion)], ranging from January 1, 2000 to June 30, 2022. VOSviewer v1.6.18, Arcgis 10.8, and HistCite pro 2.1 were used to conduct data visualization analysis. VOSviewer v1.6.18 made relevant network visualization maps of the cooperative relationship between relevant countries, institutions, and authors (co-authorship), the frequency of different keywords appearing together (co-occurrence), and the frequency of different articles cited together (co-cited). Arcgis 10.8 created the world map of publications distribution in this field and Histcite pro 2.1 was used to count the local citation score (LCS) of references. In addition, Journal Citation Reports were used to consult the latest journal import factor and JCI quartile. Results As of June 30, 2022, from the Web of Science core collection, we selected 2,474 original articles in English, excluding the document types of the news items, meeting abstracts, and some articles that had little relevance to our theme. The United States acted as the leader and enjoyed a high reputation in this field. The University of California System was the institution that made the greatest contribution (3.64% with 90 papers). Most articles were published in the Journal of Alzheimer’s Disease (8.21%, with 203 papers). The most frequently co-cited journal in Q1 was the Journal of Biological Chemistry (8,666 citations, TLS: 1039591). Russel H. Swerdlow (55 publications) was the most productive author and PH Reddy was the most co-cited author with 1,264 citations (TLS: 62971). The hotpots of mitochondrial dysfunction in AD were as follows: “oxidative stress,” “amyloid-beta-protein,” “tau,” “apoptosis,” “inflammation,” “autophagy,” “precursor protein,” “endoplasmic-reticulum,” “dynamics” and “mitochondrial unfolded protein response.” Conclusion This bibliometric analysis research will help readers rapidly identify current hotpots and milestone studies related to directions of interest in AD research.